Effects of the alimentary restriction and living space in the intake and digestive transit of naked neck chickens in grazing - Herrera, Magdalena; Gutiérrez, Odilia; Macías, J.; Savón, Lourdes; Barrera, Alexandra; Díaz, A. (Cuban Journal of Agricultural Science, 2018)
A total of 48 rustic naked neck chickens, without sexing, of T451N line, with 2.85 ± 0.99 kg of live weight and thirteen weeks of age were used to study the intake and the dynamics of transit of the diet components in three times of grazing ( 30.60 and 90 min). They were distributed according to random block design, with a 4 x 2 factorial arrangement (treatments x living spaces). The treatments were: balanced with inclusion of 3 % of mulberry meal, with four restrictions (75, 50, 25 and 0 %) in two living spaces (10 and 15 m2/bird) and supplemented with 20g / bird of California red worm. The animals with 25 % restriction obtained higher weight gain and lower food intake in 15 m2. The transit dynamics of the food registered total disappearance of the earthworms in the crop, after 60 min. There were significant effects between living space and time of filling in the digestive organs and their content. The crop and the gizzard had higher weight of the organ in 15 m2/ animal at 60 min. While, the crop increased its weight as the grazing time increased. The gizzard decreased at 90 min, when releasing the food towards the duodenum. The results suggest using 25% of food restriction in rustic Nana gene chickens, which graze in 15 m2 for 60 min, supplemented with 20 g of earthworms, to obtain weight gains similar to the control and bigger gizzards. Key words: poultry farming, earthworms, grass, digestive system